Peningkatan Kompetensi Aparatur dalam Pelayanan Pengaduan Berbasis Online di Kelurahan Kota Cimahi - Irfan Setiawan (Civitas Consecratio: Journal of Community Service and Empowerment, 2021)
Cimahi City which has a high population density, has a high impact on social problems as well. These social problems need to be handled quickly by the kelurahan as the closest government to the community. Kelurahan needs to be supported by complaints services that can be immediately accessed by the community in meeting needs and handling various problems that occur in people’s lives. These services need to be supported by officers who have competence in government services which are widely developed in the city of Cimahi. Community service activities based on research and studies aim to increase the competence of the apparatus in online-based government services in Kelurahan at South Cimahi District, especially in the field of online public complaint services. The service method goes through four stages, namely the coordination stage, the target identification stage, the data analysis stage, and the activity implementation stage. The results of community service based on research and this study indicate that there is a need to increase the competence of urban village apparatus in online public complaints services in South Cimahi District. Improvements are made so that the apparatus can understand governance in online complaint services. The need for direct socialization to the public through posters and brochures about government services online.